Pengaruh Pemberdayaan dan Perilaku Karyawan terhadap Kualitas Pelayanan Perijinan SIUP pada Dinas Perindustrian dan Perdagangan Kota Medan - Monang Sitorus (Centre for Public Policy and Management Studies, 2008)
This research analyses the influence of empowerment program and employees' behavior to the quality of services on the issuance of trade permit at Board of Industry and Trade of Medan City. This research employs theories from Clutterbuck and Kernaghan (2003), Mar'at (1981). Grand theory service quality testing writer by Denhardt and Denhardt (2003). Data are collected through a survey. The data were analyzed by using Path Analysis. The influence the empowerment (X1), to service quality (Y) is 22.3%. The influence of employees' behavior to service quality (Y) is 48.6%.Keywords: empowerment, employees behavior and service quality.